Procedimentos de pesquisa : alguns conselhos práticos para o estudo também psicolinguístico de realidades concretas - parte II - Martins, Fernanda; Pinto, Maria da Graça Lisboa Castro (Linguarum Arena, 2017)
This text comes in line with an article previously published in 2015 by the same authors on Letras de Hoje, a journal of the Pontifícia Universidade Católica do Rio Grande do Sul: “Research procedures: some practical tips aimed at studying concrete realities in psycholinguistics”. We now aim at taking the previous article further, hence the choice for the same title and its extension to a Part II. After a brief outline of what is to be expected of a research article on Applied Psycholinguistics in terms of writing and methodology, we intend to advocate the structure Introduction, Methods, Results and Discussion (IMRD) whenever texts are based on empirical data coming from diff erent areas of language studies such as didactics of languages insofar as these are domains to which Applied Psycholinguistics may bring the insights necessary to get to the roots of language learning issues. It is also our purpose to stress the originality and relevance of sections Methods and Results. Eventhough they may be considered simpler in what concerns academic writing, both sections may also be regarded as problematic as they imply a methodological framework often less familiar to researchers. Under these circumstances and bearing in mind recommendations of the scientifi c community, we intend to highlight some steps that may prove to be helpful in the process of either reading or writing academic texts in a more accurate and knowledgeable way both from the writers’ and the readers’ standpoint. By trying to answer possible questions asked by researchers who may feel doubtful when handling or interpreting experimental data, in line with the approach of the aforementioned article (Martins & Pinto 2015), this text contemplates four topics – sample selection methods, sample size, case study, and focus group – in hopes that they become less opaque